A quantitative evaluation of the flipped classroom in a large lecture principles of economics course. Issue 4 (1st October 2016) - Balaban, Rita A.; Gilleskie, Donna B.; Tran, Uyen
ABSTRACT: This research provides evidence that the flipped classroom instructional format increases student final exam performance, relative to the traditional instructional format, in a large lecture principles of economics course. The authors find that the flipped classroom directly improves performance by 0.2 to 0.7 standardized deviations, depending on the type of learning objective (i.e., knowledge, comprehension, application, or analysis). They also show that the flipped classroom improves effort during the semester, measured by in-class polling participation, and find some evidence of a heterogeneous, yet positive, effect of the flipped classroom by observable student characteristics and by level of performance.